ECOTOURISM ATTRACTIVENESS AND THE NEED TO REVIEW THE COMPETITIVENESS POTENTIAL OF ECOTOURISM DEVELOPMENT - Sulistya Rini Pratiwi; Meylin Rahmawati; Kartini Kartini (MESP–FEB UNS, 2021)
Community-based potential development in an area helps in supporting the development of a region. This research aims to analyze community-based ecotourism development strategies in Tarakan City. This study uses a qualitative method. The analytical method used is SWOT analysis (Strength, Weakness, Opportunity, Threat). The study results explain the strategy to be used in developing tourism Objects of the Persemaian in Tarakan City. is to be in quadrant II, using the strengths to take advantage of long-term opportunities to cover existing weaknesses. From the results of the SWOT analysis, it is known that the management of the area is good in improving the maintenance of infrastructure and the importance of increasing the marketing strategy to encourage the Tourism Object of the Persemaian in Tarakan City.Keywords: SWOT; Community-based ecotourism